PEMAHAMAN KONSEPTUAL SISWA DALAM MATERI OPERASI HITUNG BILANGAN BULAT KELAS VII SMP ISLAM TAZKIYAH PONTIANAK - Fahrul Azmi; Sugiatno Sugiatno; Dona Fitriawan (Jurnal AlphaEuclidEdu, 2022)
The observation aimed to determine conceptual understanding scale of the seventh grade students of SMP Islam Tazkiyah Pontianak on the material of integer operations, beside that this study intended to describe the implications of the misconceptions that occur in the material of integer operations with the answers obtained by students and describe the factors involved. Factors influenced the occurrence of misconceptions about integer operations in seventh grade students at SMP Islam Tazkiyah Pontianak. The method used in this research is descriptive. Based on the scores obtained by the research subjects, namely the seventh grade students of SMP Islam Tazkiyah Pontianak in solving conceptual understanding questions, the average percentage of achievement was 44.64%. Student representation in completing the test instrument which shows that there are misconceptions about the concept of the number line and its use in everyday life is well understood and mastered, then misconceptions on the basic concepts of the definition of integers and the properties of integers, then the occurrence of misconceptions related to the application of numbers integers in daily life and mastery of the concept of application of integer operations in daily activity.